SAS : STUDENT AWARDS SYSTEM - Nur Syazwani Atifah, Muhammad Farouk (Universiti Malaysia Sarawak (UNIMAS), 2019)
Every year during UNIMAS convocation, students who have achieve great achievement throughout their studies will receive awards. These awards are “Anugerah Diraja”, “Anugerah Canselor” and “Anugerah Pro-Canselor”. However, the manual selection nowadays is tedious and may prone to misjudgement, even though the rubrics are followed. To ensure a smooth selection and to ease the process, a system called Student Awards System (SAS) is built to filter students with great achievement and to allow student to fill in form online. With all the features provided, the proposed system will be able to ease the process of filtering students from each faculty since the process will be done online.